Role of N-acetylcysteine treatment in women with advanced age undergoing IVF/ICSI cycles: A prospective study - Li, Xiufang; Wang, Zhongqing; Wang, Huidan; Xu, Haiyan; Sheng, Yan; Lian, Fang (Frontiers in Medicine, 2022)
Objective The main objective of this study was to explore the efficacy of a new antioxidant N-acetylcysteine (NAC) supplementation in reproductive outcomes of advanced age women undergoing in vitro fertilization/intracytoplasmic sperm injection-embryo transfer (IVF/ICSI-ET), and the effect on the expression of L-glutathione (GSH) in follicular fluid (FF) and mitochondrial DNA (mtDNA) copy number of granulosa cells. Methods The present prospective randomized controlled study was conducted in 200 patients with advanced age women undergoing GnRH antagonist protocol. The treatment group (group A) consisted of 100 women who received N-acetylcysteine treatment from the menstrual phase of the previous cycle for about 45 days using the GnRH antagonist protocol. The control group (group B) consisted of 100 women who received the same protocol without N-acetylcysteine. Total gonadotrophin dosage the number of oocyte received, high-quality blastocysts, and pregnancy outcomes were compared between two groups. Pregnancy outcomes included biochemical pregnancy rate, clinical pregnancy rate, embryo implantation rate, ectopic pregnancy rate, multiple pregnancy rate, and ongoing pregnancy rate. Follicular fluid (FF) was collected after oocytes were gathered. The GSH content in the FF was tested with enzyme linked immunosorbent assay (ELISA). The mtDNA copy number of the granulosa cells was measured using real-time PCR techniques. Results Total doses of Gn in the NAC treatment group were less than those in the control group (2385.50 ± 879.19 vs. 2527.63 ± 1170.33, P = 0.047). Compared with the control, the number of high-quality blastocysts in NAC treatment increased significantly (1.82 ± 2.12 vs. 1.43 ± 1.58, p = 0.014). Clinical pregnancy rates did not differ in both groups (all P > 0.05). At the same time, the GSH content in the FF differed significantly between the two groups (1.88 ± 1.23 vs. 1.07 ± 0.70, p = 0.001). There was no significant difference in the mtDNA copy number between the two groups (P = 0.157). Conclusion A combination of NAC and Gn treatment is capable of improving the ovarian response to superovulation drugs in assisted reproductive technologies (ARTs) and also in aged populations. The addition of NAC during IVF can improve the quality of blastocysts in advanced age female subjects. However, more clinical trials are required to be designed to confirm this conclusion in future. Ethics and dissemination The experiment solicited approval from the Institutional ethics committee of the Affiliated Reproductive Hospital of Shandong University. All the participants provided written informed consent. This survey was conducted as per the Declaration of Helsinki and relevant amendments. Trial registration number www.chictr.org.cn, identifier ChiCTR2100048297.